Enhancing the Yield of a Lab-on-a-Disk-Based Single-Image Parasite Quantification Device - Vyacheslav R. Misko; Ramadhani Juma Makasali; Matthieu Briet; Filip Legein; Bruno Levecke; Wim De Malsche (Micromachines, 2023)
The recently proposed single-image parasite quantification (SIMPAQ) platform based on a Lab-on-a-Disc (LOD) device was previously successfully tested in field conditions, demonstrating its efficiency in soil-transmitted helminth (STH) egg detection and analysis on the level delivered by the current state-of-the-art methods. Furthermore, the SIMPAQ provides relatively quick diagnostics and requires small amounts of sample and materials. On the other hand, in a recent related study, it was revealed that the performance of the SIMPAQ method can be limited due to the action of the tangential Euler and Coriolis forces, and the interaction of the moving eggs with the walls of the LOD chamber. Here, we propose a new improved design that allows us to overcome these limitations and enhance the yield of the SIMPAQ LOD device, as demonstrated in experiments with a synthetic particle model system and real parasite eggs. Despite the simplicity, the proposed design modification is demonstrated to allow a substantial improvement in the yield of the SIMPAQ device, i.e., above 90% of parasite eggs and 98% of synthetic model particles were transported to the field of view. The new design proposed here will be further examined in the new generation of SIMPAQ devices within ongoing research on STH egg detection in field conditions.